Deskripsi Sistem Pengendalian Modal Kerja Pada Koperasi Guru Dan Karyawan Makmur Sejahtera SMAN 25 Bandung - Rahmadianti; Barima, Hima (Perwira Journal of Economics & Business, 2024)
This research describes the working capital control system in the teacher and employee cooperative Makmur Sejahtera SMAN 25 Bandung. This research uses descriptive research with a quantitative approach. The population in this study were all members and administrators of KGK Makmur Sejahtera SMAN 25 Bandung. The sampling technique uses simple random sampling technique or simple random sampling. The sample size in this study was 52 people obtained from the Slovin method with an error rate of 10%. The data in this research is in the form of filling out a questionnaire which then becomes information or facts. Each statement item in the questionnaire is declared valid, because the rcount is greater than the rtable value, namely greater than 0.30. Based on the research results, it can be explained that the overall response of respondents regarding the working capital control system at KGK Makmur Sejahtera SMAN 25 Bandung can be said to be good because it is in the interval 3.40 - 4.19, namely 3.74.